Uncommon Noninvasive Biomarkers for the Evaluation and Monitoring of the Etiopathogenesis of Alzheimer's Disease - Pomilio, Alicia B.; Vitale, Arturo A.; Lazarowski, Alberto J. (Current Pharmaceutical Design, 2022)
Background: Alzheimer´s disease (AD) is the most widespread dementia in the world, followed by vascular dementia. Since AD is a heterogeneous disease that shows several varied phenotypes, it is not easy to make an accurate diagnosis, so it arises when the symptoms are clear and the disease is already at an advanced stage. Therefore, it is important to find out biomarkers for early AD diagnosis that facilitate treatment or slow down the disease. Classic biomarkers are obtained from cerebrospinal fluid and plasma, along with brain imaging by positron emission tomography. Attempts have been made to discover uncommon biomarkers from other body fluids, which are addressed in this update. Objective: This update aims to describe recent biomarkers from minimally invasive body fluids for the patients, such as saliva, urine, eye fluid or tears. Methods: Biomarkers were determined in patients versus controls by single tandem mass spectrometry and immunoassays. Metabolites were identified by nuclear magnetic resonance and microRNAs with genome-wide high-throughput real-time polymerase chain reaction-based platforms. Results: Biomarkers from urine, saliva, and eye fluid were described, including peptides/proteins, metabolites, and some microRNAs. The association with AD neuroinflammation and neurodegeneration was analyzed, highlighting the contribution of matrix metalloproteinases, the immune system and microglia, as well as the vascular system. Conclusion: Unusual biomarkers have been developed, which distinguish each stage and progression of the disease, and are suitable for the early AD diagnosis. An outstanding relationship of biomarkers with neuroinflammation and neurodegeneration was assessed, clearing up concerns about the etiopathogenesis of AD.
Keywords: Alzheimer’s disease